Addition of thrombin reduces the recovery of extracellular vesicles from blood plasma - Anush Arakelyan; Wendy Fitzgerald; Murad Vagida; Elena Vasilieva; Leonid Margolis; Jean-Charles Grivel (Journal of Circulating Biomarkers, 2016)
Extracellular vesicles (EVs) are widely studied as a system of intercellular communication, as markers of various diseases, as well as a vehicle for delivery of various bioactive molecules to various cells. Investigation of EVs’ structure and function requires their isolation and precise quantification. However, in the current literature, there are significant discrepancies in the estimated numbers of EVs in different body fluids. In part, this discrepancy is due to the difference in EVs isolation protocols used by different investigators. A common protocol that includes ExoQuick ™ is often used to isolate EVs from body fluids and culture medium. Here, we show that in the case of isolation of EVs from blood, thrombin should be omitted from the protocol as clots formed due to the thrombin-triggered coagulation may entrap many EVs thus leading to the underestimation of their numbers.